Reprezentări și funcții ale sânzienelor în proza românească. Scurt studiu comparativ / REPRESENTATIONS AND FUNCTIONS OF THE MIDSUMMER NIGHT’S FAIRIES IN ROMANIAN FICTION. A SHORT COMPARATIVE STUDY - Alina Bako (Incursiuni în imaginar)
The integration of the image of Midsummer Night’s Fairies (Sânziene) in Romanian fiction is related to the folk-type myth, present in the writings of authors such as Mihail Sadoveanu and Mircea Eliade. Even if this is the element around which the narrative patterns coagulate, the image becomes a formula, a scheme that some events contain only like a sequence of the original myth. The use of myths is achieved in a different way, on the one hand by recording a kind of closeness and regression conceived as a primordial story – as in Sadoveanu's novel – and, on the other hand, by increasing the sense of femininity and the faith in the formation of a couple, with repetitive forms, just like any mythical scenario, in Mircea Eliade's text.